Application of 3D bio-printing for skin repair - Jinyuan MA; Yaobin WU; Wenhua HUANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
The skin is the largest organ of the human body, and its structural integrity plays a crucial role in the maintenance of the normal physiological function of the human body. The repair of large skin trauma and the healing of chronic skin ulcers are clinical problems to be solved. Although great progress has been made in the field of skin tissue engineering over the last decades, it is still a challenge to develop the engineered skin by incorporating with skin appendages, such as hair follicles, sweat glands, sebaceous glands and vascularization. However, 3D bio-printing technology provides a potential to solve these problems. In this review, we briefly discuss the application, prospective, and challenges of 3D bio-printing technology in skin wound repair.